Adenosine A(2A) receptors in portal hypertension - de Brito, MTV (2015)
1 Adenosine is a regulator of mesenteric vasodilation involved in auto-regulation and post-prandial hyperemia. but the adenosine receptor subtype involved in this relaxant effect is poorly characterized. We have now, pharmacologically characterized this receptor in rabbit mesenteric arteries and investigated how this adenosine receptor, response changes in portal hypertensive animals since the adenosine response is decreased. 2 The closest non-metabolisable adenosine analogue. 2-chloroadenosine (CADO), the mixed A(1)/A(2) receptor agonist. 5'-ethylcarboxamidoadenosine (NECA), and the selective A(2A) receptor agonist, 2-[4-(2-p-carbonyethyl)phenylamino]-5'-N-ethylcarboxainidoadenosine (CGS 21680) (1 pM - 1 mM) relaxed noradrenaline pre-contracted arteries with a rank order of potency of CGS 21686 (EC50 = 20 nM) greater than or equal to NECA (60 nM) CADO (640 nM). 3 The selective A(2A) receptor antagonist, 4-(2-[7-amino-2-(2-furyl)-[1,2,4]-triazolo[2,3-a][1,3,5]triazin-5-ylamnino]ethyl)phenol (ZM 241385. 100 nM), shifted to the right the CADO concentration-response curve. 4 In portal hypertensive animals, there was mainly a decreased potency but also a decreased efficacy of all tested adenosine agonists compared to normal animals. Concomitantly. there was a decreased adenosine plasma level and a decreased binding density of [H-3]-CGS 21686 and [H-3]-ZM 241385 to mesenteric artery membranes from portal hypertensive compared to normal rabbits. 5 These results indicate that A(2A) receptor activation is required for the adenosine-induced mesenteric relaxation and that the decreased density of A(2A) receptors may contribute to the decreased relaxation induced by adenosinc of mesenteric arteries in portal hypertensive animals. British Journal of Pharmacology (2002).